Un sabor a moras - Smith, Doris Buchanan; Jimenez Rioja, Alberto (New York, NY : Lectorum Publications, 2002)
En esta novela el nino Jamie muere y su mejor amigo tiene que encarar solo la tragedia.
A young boy recounts his efforts to adjust to the accidental death of his best friend.
Keywords: Friendship -- Fiction; Death -- Fiction; Spanish language materials -- Fiction; Fiction